Сьод валъес: повесть, веросъес, гожтэтъес / Н. С. Байтеряков - Байтеряков Н. С. (Удмуртия, 1995)
Экземпляры: ф.14 (20150420) / Инвентарный номер: 35511 / Цена: 10. 00. / Сис.шифр: С(Удм) / Авт.знак: Б 18 / ГРНТИ: 17.82.32 / ББК: 84(2 Рос.=Удм)-44